X-ray, IR and Raman study of Ag(I), Cu(II) and Cd(II) complexes with 4, 5-bis(N, N-di(2-hydroxyethyl)iminomethyl)acridine. (26th February 2016) - Solovyeva, Elena V.; Starova, Galina L.; Myund, Liubov A.; Denisova, Anna S.
Graphical abstract: New complexes of 4, 5-bis(N, N-di(2-hydroxyethyl)iminomethyl)acridine have been prepared and studied by using techniques including X-ray single crystal, IR and Raman spectroscopy. The three different coordination manners of the molecule were found depending on metal cation and anion. Abstract: Five new 1:1 metal complexes of highly selective acridine-based fluorophore 4, 5-bis(N, N-di(2-hydroxyethyl)iminomethyl)acridine (BHIA) with Ag(I), Cu(II) and Cd(II) were synthesized, characterized and investigated by the methods of single crystal X-ray diffraction, IR, and Raman spectroscopy. Single crystal X-ray analysis reveals that three different coordination manners of the BHIA occur. Five atoms of the BHIA molecule take part in the formation of complex with Ag(I) and six atoms are involved in the formation of complex with Cu(II). In the case of BHIA with Cd(II) interaction, the coordination possibilities of the cation depend on an anion and vary from five to seven. The investigation of BHIA complexes by IR and Raman spectroscopy shows that if there are two free hydroxyl groups in the molecule then the vibrational spectrum arises from many rotational conformations. The different binding manner of BHIA molecule with metal cations is the most clearly manifested in the IR spectrum in the region of the stretching OH-vibrations.